Biopolymer as alignment layer for liquid crystal mixtures. (2nd November 2017) - Spadło, Anna; Bennis, Noureddine; Węgłowski, Rafał; Węgłowska, Dorota; Czuprynski, Krzysztof; Otón, José M.
ABSTRACT: Biopolymer alignment layers like deoxyribonucleic acid (DNA) derivatives are used to orient different types of liquid crystal (LC) molecules to produce devices for applications that require lower curing temperatures. The LC surface interaction with the double-stranded helical DNA aligned film is an interesting challenge for LC materials developing. The unique properties of DNA materials, derived from a double-helix structure, are very promising for photonics and molecular electronics applications, for they feature excellent optical and physical properties.